HUMAN CAPITAL MANAGEMENT AND FACTORS OF ITS DEVELOPMENT - Ochilov, Djumaev, Muratov, Alimardonova, Akram Odilovich, Yashin Tursunalievich, Azam Alisher ugli, Gulfizoda Alimardon kizi (THE INNOVATION ECONOMY, 2024)
The article describes the concept of human capital, the features of its formation, its essence, the goals of human capital development in determining the development strategy of the Republic of Uzbekistan and the direction of the factors of its development. In addition, the article analyzes the approaches of foreign and domestic scientists to human capital, the results of their research, and based on the findings obtained, appropriate recommendations are given.